2017
DOI: 10.1534/g3.117.042697
|View full text |Cite
|
Sign up to set email alerts
|

A Duplicated, Truncated amh Gene Is Involved in Male Sex Determination in an Old World Silverside

Abstract: A master sex-determining gene, the Y chromosome-linked anti-Müllerian hormone (amhy) gene, has been described in two New World atheriniform species but little is known on the distribution, evolution, and function(s) of this gene in other Atheriniformes. Interestingly, amhy has been found to coexist with temperature-dependent sex determination (TSD), providing a unique opportunity to explore the interplay between genotypic and environmental sex determination. In this study, the search for an amhy homolog was ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
47
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 37 publications
4
47
0
Order By: Relevance
“…Because the conserved Amh domains that are altered in the amhby genes in these two species are needed for proper protein secretion and interaction between Amh and its receptor 3 , it is unclear how these truncated Amhby proteins could still serve as functional MSD proteins. A similar duplication and truncation of an amh MSD gene has already been reported in the cobaltcap silverside (Hypoatherina tsurugae), another teleost 22 . In addition, other cases of MSD genes having evolved through duplication / truncation of their ancestral copy have also been described, such as the sdY MSD gene in Salmonids and the putative amhr2by MSD gene in yellow perch, Perca flavescens, demonstrating that preservation of all ancestral domains is not always necessary for a duplicated protein to assume an MSD role 13,23,24 .…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Because the conserved Amh domains that are altered in the amhby genes in these two species are needed for proper protein secretion and interaction between Amh and its receptor 3 , it is unclear how these truncated Amhby proteins could still serve as functional MSD proteins. A similar duplication and truncation of an amh MSD gene has already been reported in the cobaltcap silverside (Hypoatherina tsurugae), another teleost 22 . In addition, other cases of MSD genes having evolved through duplication / truncation of their ancestral copy have also been described, such as the sdY MSD gene in Salmonids and the putative amhr2by MSD gene in yellow perch, Perca flavescens, demonstrating that preservation of all ancestral domains is not always necessary for a duplicated protein to assume an MSD role 13,23,24 .…”
Section: Discussionsupporting
confidence: 75%
“…), poeciliids, tilapiine cichlids, salmonids, and sticklebacks, in which different SD systems, sex chromosomes and MSD genes were found even in closely related species [14][15][16][17][18] . Apart from the Oryzias family [19][20][21][22][23][24][25][26][27][28][29] and the salmonids 18,[30][31][32] , however, relatively few studies have explored the evolution of SD systems and the fate of MSD genes within an entire group of closely related species.…”
Section: Introductionmentioning
confidence: 99%
“…bonariensis , the sister species of the Patagonian pejerrey, a male-specific amhy was found to interact with temperature in determining sex [19], and in the ling cod, Ophiodon elongatus , a male-specific duplicate of amh was also identified using molecular marker sequences [43]. More recently, a duplicated copy of amh was found in an Atheriniformes species, Hypoatherina tsurugae , and is suspected to be involved in male sex determination [44]. Besides amh , its canonical receptor, amhrII , has also been shown to play a pivotal role as a MSD gene in the Tiger Pufferfish, Takifugu rubripes [45].…”
Section: Discussionmentioning
confidence: 99%
“…Besides these three examples, association of amh duplicates with phenotypic sex was also found in other teleosts: in O. bonariensis , the sister species of the Patagonian pejerrey, a male-specific amhy was found to interact with temperature in determining sex [19], and in the ling cod, Ophiodon elongatus, a male-specific duplicate of amh was also identified using molecular marker sequences [43]. More recently, a duplicated copy of amh was found in an Atheriniformes species, Hypoatherina tsurugae, and is suspected to be involved in male sex determination [44]. Our phylogenetic analysis on Amh sequences from several teleost species revealed that the three confirmed male-specific Amh duplications are independent, lineage-specific events rather than the product of shared ancestry.…”
Section: Discussionmentioning
confidence: 99%